2020
DOI: 10.1111/sltb.12614
|View full text |Cite
|
Sign up to set email alerts
|

Who Is at Risk of Dying Young from Suicide and Sudden Violent Death? Common and Specific Risk Factors among Children, Adolescents, and Young Adults

Abstract: Objective Suicides and other sudden violent deaths are the most common causes of death among young people worldwide. This case–control study compared risk factors for suicide and other sudden violent death among young people. Method A total of 436 psychological autopsy interviews with next of kin were performed. The samples aged 10–25 years included 63 cases of suicide, 62 cases of other sudden violent death, and 104 matched living controls. Two stepwise multiple logistic regression analyses were performed. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…Existing literature has pointed to various risk factors for suicide, such as stressful life events [ 23 ], isolation and loneliness [ 24 ], substance abuse [ 25 ], and psychological distress [ 26 ]. A meta-analysis of 50 years of research on suicidality [ 27 ] suggests that previous studies on risk factors are homogeneous and there have been mixed findings on the temporal associations between psychological distress and suicidal ideation [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Existing literature has pointed to various risk factors for suicide, such as stressful life events [ 23 ], isolation and loneliness [ 24 ], substance abuse [ 25 ], and psychological distress [ 26 ]. A meta-analysis of 50 years of research on suicidality [ 27 ] suggests that previous studies on risk factors are homogeneous and there have been mixed findings on the temporal associations between psychological distress and suicidal ideation [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, comorbid mental disorder and substance abuse preceded suicide in more cases than controls. An analysis of the multivariate effects of the potential risk factors found that the common risk factors for suicide were addiction, inpatient adult psychiatric care, and the number of stressful life events [ 15 ]. The available research data in the present study were not sufficient to draw a conclusion regarding the influence of a certain disease or sociological variable on suicide.…”
Section: Discussionmentioning
confidence: 99%
“…The depressive type showed a higher percentage of diagnosis of mental disorder compared to the other two groups, as well as a history of suicidal attempts. However, interestingly, a Swedish study that performed psychological autopsy of 63 cases of suicides aged 10–25 years found that 49.2% had never made a previous suicidal attempt [ 15 ]. The warning signs (verbal, behavioural, and emotional) before suicide were observed in the depressive type to a significantly higher degree than in the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 104 control cases, 76 were men (73.1%) and 28 women (26.9%), aged 10-25 years (M = 20.7; SD = 3.4). Detailed sociodemographic, psychosocial and psychiatric data for the three samples, as well as previous suicide attempts, suicide methods and cause of sudden violent death are presented in a previous publication (47). However, it is worth noticing here that 71% of the cases of suicide, 58% of the cases of SVD, as well as 47% of the controls had received some form of help from mental health services.…”
Section: Participantsmentioning
confidence: 99%
“…To sum up, the number of potential risk factors is large, the relationships between them are complicated, and in each case we encounter unique, idiosyncratic combinations of fixed and variable, proximal, distal, and mediating variables (20,46). In a previous study, we examined common and specific risk factors for dying young from suicide and other forms of sudden violent death (47). We found that borderline personality disorder was associated with both causes of death; depression spectrum disorder was associated with death by suicide, whereas antisocial personality disorder was associated with sudden violent death.…”
Section: Introductionmentioning
confidence: 99%